Estimating Input Demand Equations by Direct and Indirect Methods - Wills, H. R. (Review of Economic Studies, 1981)
Journal Article Estimating Input Demand Equations by Direct and Indirect Methods Get access H. R. Wills H. R. Wills London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 2, April 1981, Pages 255–270, https://doi.org/10.2307/2296883 Published: 01 April 1981 Article history Received: 01 January 1979 Accepted: 01 November 1980 Published: 01 April 1981